An ethnopoetic analysis of master of ceremonies' vocal beauty in Javanese weddings - Efendi, Anwar; Winantaka, Binar; Yue, Xiong; Dwijonagoro, Suwarna (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
The vocal beauty play a vital role in the master of ceremonies (MC) profession. This study explores and elaborates the vocal exercises of MCs in Javanese weddings. The data were collected by recording the speeches of three leading MCs in Yogyakarta, Indonesia. In this study, the researcher was the key instrument. The data were validated by material experts and ten MCs from Yogyakarta MC Community (Paguyuban Pranatacara Yogyakarta, PPY) in a focus group discussion (FGD). The ethnopoetic analysis was carried out focusing on the beauty of the text and vocal. While the text was described descriptively, the vocal was elaborated using notation. The data analysis steps included transcription, identification, codification, classification, description and interpretation, elaboration, and inference. The findings show that (1) vocal exercises are more important than linguistic and literary, physical, or wear-matching exercises; (2) vocal exercises can be done both physically and mechanically; (3) vocal exercises depend on the wedding ceremony type/style, situation, and the existence of gending (Javanese orchestral composition); (4) there are three main types of vocal exercises: lamba song, candra song, and tembang (sung poerty); (5) lamba can be sung by MC in many different ceremonies, situations, places, laras (scale), pathet (mode), and gending; (6) candra song has to be accompanied by gending, either ladrang or ketawang; (7) tembang can be performed in solo, semi-collaboration, or collaboration; and (9) polyharmony occurs when there is a harmony among MC's tones, gamelan's laras and tones, and waranggana's (female singers) tones.